2010
DOI: 10.1186/1471-2407-10-374
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between H.Pylori infection and clinicopathological features and prognosis of gastric cancer

Abstract: BackgroundAimed to assess the relationship between H.Pylori and the clinicopathological features and prognosis of gastric cancer by quantitative detection of H.Pylori.Methods157 patients were enrolled, all patients had a record of clinicopathological parameters. Specimens including the tumor and non-neoplastic were detected for H.Pylori by Real-Time PCR and analyzed clinical data retrospectively. Variables independently affecting prognosis were investigated by means of multivariate analysis using the Cox propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 38 publications
3
43
5
Order By: Relevance
“…In agreement with most studies in the literature, we found that the rate of H. pylori positivity was higher in non-neoplastic tissue than in tumour tissue 18 . The possible biologic basis might be elucidated as follows: Once cancer developed, sustained injury to the gastric mucosa persisted.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In agreement with most studies in the literature, we found that the rate of H. pylori positivity was higher in non-neoplastic tissue than in tumour tissue 18 . The possible biologic basis might be elucidated as follows: Once cancer developed, sustained injury to the gastric mucosa persisted.…”
Section: Discussionsupporting
confidence: 82%
“…An overall positivity rate of 72.0% was observed in our patients. That value is higher than the rates reported in other Asian studies 18,26 , which might be explained by epidemiologic factors and the sensitivity of the various methods used to detect H. pylori infection. Moreover, it is well known that a high prevalence of H. pylori is always accompanied by a high incidence of gastric cancer 27 .…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…H. pylori was more prevalent in nontumor tissue, and its presence was related to tumor site and N-stage, whereas there was no correlation to overall or recurrence-free survival after curative surgery [26].…”
Section: H Pylori As High Risk Indicatormentioning
confidence: 93%